Cognitive Behavioral Counseling to Overcome Anxiety Facing Exams: A Quasi-Experimental Study on SMA Negeri 2 Pagaden Students - Siti Nuriah; Muhammad Adzroi; Ahman Ahman; Irfan Fahriza; Tea Septina (Ma'soem University, 2024)
This research aimed to produce cognitive behavioral counseling services which are effective to help students overcome anxiety in facing the exam. The research used a quantitative approach and quasi-experimental research design nonequivalent pretest-posttest control group design. The research was conducted at SMA Negeri 2 Pagaden with the first semester students were taken randomly as research subject. The research instrument that was used was Anxiety Scale in facing exam. The results showed empirically, a cognitive behavioral counseling intervention has proven effective to overcome anxiety in students